Apigenin Inhibits the Histamine-Induced Proliferation of Ovarian Cancer Cells by Downregulating ERα/ERβ Expression - Liu, Manman; Zhang, Yani; Xu, Qiqi; Liu, Guirong; Sun, Na; Che, Huilian; He, Tao (Frontiers in Oncology, 2021)
Background Apigenin (APG), a natural flavonoid, can affect the development of a variety of tumors, but its role in ovarian cancer remains unclear. There has been an increasing amount of evidence supporting the vital role played by mast cells and the bioactive mediators they release, as components of the tumor microenvironment, in the progression of ovarian cancer (OC); however, the mechanism warrants further exploration. Methods and Results In this study, a combination of transcriptomics analysis and application of TCGA database was performed, and we found that the expression of genes related to mast cell degranulation in ovarian cancer tissues changed remarkably. We then explored whether histamine, a major constituent of mast cell degranulation, could affect the development of ovarian cancer through immunohistochemistry analysis and cell proliferation assays. The results showed that a certain concentration of histamine promoted the proliferation of ovarian cancer cells by upregulating the expression of estrogen receptor α (ERα)/estrogen receptor β (ERβ). Additionally, we found that the inhibition of ERα or the activation of ERβ could inhibit the proliferation of ovarian cancer cells induced by histamine through real-time PCR and western blot assays. Finally, we demonstrated the attenuation effect imparted by apigenin in histamine-mediated ovarian cancer via the PI3K/AKT/mTOR signaling pathway. Conclusion Our research revealed that apigenin decelerated ovarian cancer development by downregulating ER-mediated PI3K/AKT/mTOR expression, thus providing evidence of its applicability as a potentially effective therapeutic agent for ovarian cancer treatment.